THE EFFECT OF THE PROJECT BASED LEARNING MODEL BASED ON THE LOCAL WISDOM OF BALI MENYAMA BRAYA ON SCIENCE LEARNING OUTCOMES AS SEEN IN THE FACULTY OF STUDENTS' ACHIEVEMENT MOTIVATION IN GRADE V OF ELEMENTARY SCHOOL GUGUS 2 TAMPAKSIRING - I Wayan Wirjanata; Ida Bagus Putu Arnyana; I Ketut Gading (RADJA PUBLIKA, 2026)
This study aims to examine the effect of the project based learning model based on Balinese local wisdom Menyama Braya on the learning outcomes of science in terms of the achievement motivation of fifth grade students of Elementary School Cluster 2 Tampaksiring, Tampaksiring District in the 2025/2026 academic year . This type of research is a quasi-experimental study using a posttest only control group design with a 2 × 2 factorial design . The population of this study was fifth grade in Cluster 2 Tampaksiring, Tampaksiring District in the 2025/2026 academic year, totaling 184 people . Data were collected using a questionnaire method to measure achievement motivation and a test to measure learning outcomes. The collected data were analyzed using two-way ANOVA. Based on the results of the data analysis, it was obtained: 1) there was a significant influence on the learning outcomes of students who followed the PjBL learning model based on Balinese local wisdom Menyama Braya , this was evidenced by the value (sign = 0.045, p <0.05). 2) There is an interaction between the learning model and motivation on the results of learning science, this is evidenced by the value (sign = 0.000, p <0.05). 3) In the group of students who have high achievement motivation, there is an influence of the Project Based Learning learning model based on Balinese local wisdom Menyama Braya on the results of learning science of grade V students of Elementary School Cluster 2 Tampaksiring, this is evidenced by the value (sign = 0.000, p <0.05). 4) In the group of students who have low achievement motivation, there is an influence of the Project Based Learning learning model based on Balinese local wisdom Menyama Braya on the results of learning science of grade V students of Elementary School Cluster 2 Tampaksiring, this is evidenced by the value (sign = 0.028 , p <0.05).